Emphasizing the Borderlands in a Future Central European Educational Programme - Taborska, Katarzyna (Porównania, 2021)
The present paper is an attempt at including elements of cosmoecology in humanistic education on borderlands. The composition of the paper was inspired by the reading of the edited volume Na pograniczu narodów i kultur. Polska – Europa – Ameryka [On the borderlands of nations and cultures. Poland – Europe – America] (eds. B. Wróblewski, Ł. Janicki, Warszawa-Lublin 2020). The goal of the article is to present preliminary assumptions for possible educational discourses on the borderlands in a holistic approach, which will provide for the dependencies and mutual influence of cultures in the diachrony and synchrony of ecosystems. The author puts forward the introduction of terminology related to natural sciences as a tool for describing relationships on borderlands and presents her reflections on liquid intra-environmental borderlands as well as an ecocritical approach to colonization.